Microbial Communities of Low Temperature, Saline Groundwater Used for Therapeutical Purposes in North Poland. Issue 3 (16th March 2019) - Kalwasińska, Agnieszka; Deja-Sikora, Edyta; Szabó, Attila; Krawiec, Arkadiusz; Felföldi, Tamás; Swiontek Brzezinska, Maria; Walczak, Maciej
Abstract: Knowledge on microbial community composition and ecology in highly mineralized (TDS up to 71 g l −1 ), cold waters (T < 12 °C) from the zones of restricted water exchange is scarce. Therefore, the aim of our study was to reveal how the particular physicochemical water conditions of these zones affect the community composition. The community members, which could be involved in the sulfur cycling were of particular interest since they may strongly influence wells operation. The pristine, mineral waters of North Poland were extracted from boreholes reaching Cenozoic, Jurassic, and Triassic aquifers at the depth of 46–1248 m below ground surface. Both culture-dependent (culturing on R2A medium) and culture-independent techniques (microscopic methods and high-throughput 16S rDNA amplicon sequencing) were applied. The bacterial communities were characterized by low complexity and strongly varied across the sampling locations. Bacteria potentially involved in the sulfur cycle (sulfate reduction) were common in all mineral waters and were dominant (especially Desulfovibrio ) in the deepest waters. The most important geochemical drivers of the observed microbial community composition were TDS including Cl −, Na +, Mg 2+, and NO3 − . Bacterial isolates belonged mostly to the genus Bacillus . Sequences assigned to Archaea ( Methanobacterium ) were detected only in the deepest borehole water.